2018
DOI: 10.7250/bjrbe.2018-13.414
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Assessment of Lithuanian Road Accidents by AHP Method

Abstract: Lithuanian road accidents were evaluated based on the geographic information systems and multi-criteria method of Analytical Hierarchy Process This paper presents the methodology for selecting and ranking high accident concentration sections on the roads of national significance. Methodology involves the following process phases: 1) preparation of spatial data of the road accidents; 2) estimation of road sections with a high accident rate; 3) calculation of spatial statistics for estimation of accident points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…AHP метода је широко примењена у саобраћају. Једна је од најчешће коришћених вишекритеријумских метода у избору решења у планирању [10], пројектовању, одржавању [11], реконструкцији саобраћајне инфраструктуре [12] и безбедности саобраћаја [13,14].…”
Section: методологијаunclassified
“…AHP метода је широко примењена у саобраћају. Једна је од најчешће коришћених вишекритеријумских метода у избору решења у планирању [10], пројектовању, одржавању [11], реконструкцији саобраћајне инфраструктуре [12] и безбедности саобраћаја [13,14].…”
Section: методологијаunclassified
“…The land cover change (a 0.48% change rate per year) in the country is slowing, mainly due to a rapid decrease in the intensity of forest conversion [58]. In 2017, there were 21,244 km of State-owned roads of national significance (excluding roads in cities): 1751 km of main roads; 4925 km of national roads; and 14,568 km of regional roads [59]. In this study, we analysed 1784 roads (21 main/highway, 13 national, and 1631 regional) as shown in Figure 1.…”
Section: Study Areamentioning
confidence: 99%
“…In the period 2002-2017, the annual average daily traffic (AADT) increased from 5600 to 11,000 vehicles a day on main roads, from 2200 to 2900 vehicles a day on national roads, and remained at up to 500 vehicles a day on regional roads [60]. In 2017, there were 21,244 km of State-owned roads of national significance (excluding roads in cities): 1751 km of main roads; 4925 km of national roads; and 14,568 km of regional roads [59]. In this study, we analysed 1784 roads (21 main/highway, 13 national, and 1631 regional) as shown in Figure 1.…”
Section: Study Areamentioning
confidence: 99%
“…Hajeeh (2012) presented the number of violations and car accidents in the period 2000-2009 and by using the AHP method found that in order to solve traffic problems in Kuwait, it is necessary to reduce the number of traffic accidents and congestion. Analysis of traffic accidents (2013)(2014)(2015)(2016)(2017) is also illustrated in research by Jakimavičius (2018) where the author used the AHP method for ranking road sections and the result presents 3 most dangerous sections, which are identified as black spots. Anđelković et al (2018) have presented a new statistical model for the identification of dangerous locations (subsections) on roads, also known as hotspots.…”
Section: Introductionmentioning
confidence: 99%